POLA PERUBAHAN TEKANAN DARAH BERDASARKAN INDEKS MASSA TUBUH PADA WANITA MENOPAUSE - Indraswari, Yunita Herliana; Sasmito, Lulut; Restanty, Dian Aby (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2024)
Metabolic disease is seen in women over 50 years of age who have gone through menopause. The prevalence of hypertension according to WHO 2019 is 29%. One of the indicators determining hypertension is body weight. The measuring tool to determine obesity is the calculation of body mass index. The prevalence of hypertension in Indonesia in women is 36.85%, East Java Province 51.2%, and Based on Data from the Jember Regency Health Office in 2023, especially in women in the Jember Kidul Health Center work area, it reached 19.35%. This study aims to determine the pattern of changes in blood pressure based on body mass index in menopausal women. This study took place in the Jember Kidul Health Center Work Area which was conducted on March 1-May 30, 2024. The research design used observational analytics with a prospective cohort approach. The population was 112 menopausal women over 50 years of age, sampling using purposive sampling, namely 53 respondents. Data collection using a questionnaire. Data analysis with Simple Linear Regression test. The results of the study showed that the pattern of blood pressure changes followed the body mass index in menopausal women with a ?-value <? 0.05. There were changes in BMI caused by the frequency of eating, work, and physical activity for 3 weeks, which resulted in changes in blood pressure in menopausal women